Research Status of Composite Thin Spray Materials - Han, Yulong (International Journal of Natural Resources and Environmental Studies, 2026)
In order to adapt to the development of The Times, reduce the construction amount of workers and meet the requirements of intelligent roadway construction, there is an urgent need for a new material to solve the existing problems of the existing support materials. Thin spray material is a kind of polymer cement based material, which has the effect of preventing weathering of surrounding rock, spontaneous combustion of coal seam, harmful gas sealing, preventing corrosion of metal support and supporting of surrounding rock. This paper mainly summarizes the research progress of thin spray materials in recent years and the mechanical properties and sealing properties of thin spray materials, finds the problems of existing thin spray materials in the market and puts forward their own views, and finally prospects the future of thin spray materials.